Strengthening companies’ competitive position from Tawhidic paradigm: the experience of bursa Malaysia listed companies - Mhd. Sarif, Suhaimi (International Journal of Business, Economics and Law - IJBEL, 2016)
This paper examines possible strategies from Tawhidic Paradigm in strengthening the generic competitive strategies of UMS Holdings Berhad, United U-Li Corporation Berhad, Damansara Realty Berhad, and Dutch Lady Milk Industries Berhad. Three elements are used for the assessment, the current competitive position, timing moves, and scope of operations. The recommended approaches are based on the competitive advantage and the market target of the companies. The results of Internal and External Factors Analyses are combined into a matrix to depict possible broad decisions and actions, whether to build and grow, hold and maintain, or harvest and divestiture. The assessment of Tawhidic paradigm is based on the ibadah, aqidah and akhlak elements. The results of the study suggest the strategic options proposed and used by the companies are practical yet cautioned with the changes in the market. The study suggests further research with personal interview and case study methods with more participants.